Influence of education and socio-economic status on physical activity of adult residents of regions Eastern Bohemia and Vysocina between 2005-2009 - Dana Feltlová; Josef Mitáš; Lucie Kubíčková; Karel Frömel; Pavel Šmíd; Jan Dygrýn (Tělesná Kultura, 2011)
BACKGROUND: Physical activity (PA) promotion is one of the most important factors in prevention of non-infectious civilization diseases. Other factors that may affect PA (economical, environmental, socio-cultural, etc.) are intensively monitored in relation to the quality of life. Regionally related conditions for the realization of leisure PA can improve the differences in the level of PA in different population groups. AIMS: The aim of this study was to analyze physical activity of the population of the Eastern Bohemian region (Hradec Králové, Pardubice and Vysočina) regarding the education and socioeconomic status. METHODS: Term "Eastern Bohemian" region was used to sum the data collected from regions of Hradec Králové, Pardubice and Vysočina. To determine the weekly level of PA we used a randomized data set of 1273 people from the Eastern Bohemian region (555 men and 718 women) aged 41.03 ± 9.16 years. All respondents were asked personally by educated distributors (university students) to participate in a research study using the Czech version of the IPAQ questionnaire. Data collection was carried out regularly in Spring (March-May) and Autumn (September-November) period from 2005 to 2009. RESULTS: People with higher education (university degree) have a lower amount of weekly PA than people with lower type of education (primary and secondary). People with secondary school education reported the highest amount of realized PA. There is diversified socioeconomic status (SES) in the Eastern Bohemian region. People with higher SES reported a lower level of realized PA than people with lower SES. CONCLUSIONS: The high loss of PA in university educated population is an alarming indicator of possible health complications. This group should be targeted in prevention health programs. Natural attractiveness should be maintained and opportunities made available for the realization of cultural, cycling and hiking trips. Programs motivating local people to carry out leisure PA should be adapted.